Sự gắn kết của sinh viên và chất lượng cuộc sống đại học: Nghiên cứu thông qua giá trị dịch vụ cảm nhận và mục đích cuộc sống - Nguyễn Thị Đoan, Trân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This article aims to empirically examine the factor of student engagement in the university in which they enroll, in order to demonstrate the relationship of student engagement to the quality of college life. Also found and justified in this study are perceived service value and purpose in life, two important antecedent variables of student engagement, of which the evidence was scarce in earlier literature. By applying Structural Equation Modeling to process the model with four latent variables and five hypotheses relating to the linkages among these variables, the research results suggest that four out of five hypotheses are accepted at the significance level of 0.1% with official data collected from 829 students at two college institutions for economics and business education (perceivably ranked top) in Hanoi.